Identification of four secondary acyltransferases for lipid A biosynthesis in Vibrio parahaemolyticus. (16th November 2020) - Zhou, Qing; Tan, Xin; Meng, Xiangyu; Wang, Jianli; Ji, Fan; Wang, Xiaoyuan
Abstract: In this study, four genes encoding secondary acyltransferases of lipid A in Vibrio parahaemolyticus ATCC33846 were identified. When the four genes were overexpressed in Escherichia coli MLK1067 that which produces the penta‐acylated lipid A lacking the secondary acylation at the C3′ position, a C12:0 secondary acyl chain was added at the C3′ position of lipid A only in E. coli overexpressing VP_RS01045, but not VP_RS00880, VP_RS08405, or VP_RS12170 . When the four genes were overexpressed in E. coli MKV15b that produces lipid IVA, a C12:0 secondary acyl chain was again added at the C3′ position in E. coli overexpressing VP_RS01045, but a C14:0 secondary acyl chain was added at the C2′ position of lipid A in E. coli overexpressing VP_RS00880, VP_RS08405, or VP_RS12170 . The results indicate that four acyltransferases of lipid A are encoded by VP_RS01045, VP_RS00880, VP_RS08405, or VP_RS12170 in V. parahaemolyticus . The acyltransferase encoded by VP_RS01045 adds a C12:0 secondary acyl chain at the C3′ position of lipid A, whereas the acyltransferase encoded by VP_RS00880, VP_RS08405, or VP_RS12170 adds a C14:0 secondary acyl chain at the C2′ position of lipid A. This work contributes to understanding the biosynthetic pathway of lipid A in V. parahaemolyticus . Abstract : The functions of four lipid A acyltransferases encoded by VP_RS01045, VP_RS00880, VP_RS08405 and VP_RS12170 in vibrio parahaemolyticus were confirmed in Escherichia coli .